THE INFLUENCE OF INTELLECTUAL INTELLIGENCE AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION - Gilliani, Gratiani; Rahardjo, Mukti (International Journal of Application on Economics and Business, 2023)
The success of PT Fast Food Indonesia Tbk. in becoming the best fast food restaurant brand in Indonesia, as mentioned on the Top Brand website from 2020 to 2022, is certainly supported by highly performing human resources. This situation sparks the researchers' curiosity to analyze the influence of intellectual intelligence and emotional intelligence and job satisfaction as an intervening variable on employee performance. The data was collected through the distribution of questionnaires using a google form. A total of 100 respondents were included in the sample for analysis. SmartPLS software with PLS-SEM approach is used in this analysis. According to the findings of this study, intellectual intelligence and emotional intelligence have a significant and positive effect on job satisfaction. Intellectual intelligence, emotional intelligence and job satisfaction also have a significant and positive effect on employee performance. Job satisfaction can meditate the influence of intellectual intelligence and emotional intelligence on employee performance.